Simple setup for rapid testing of third-order nonlinear optical materials - BLAU, WERNER (My University, 1990)
A relatively inexpensive and versatile degenerate four-wave mixing setup is described utilizing a nitrogen laser pumped dye laser. Samples can be screened rapidly, which is demonstrated with the example of a semiconductor doped glass having a nonlinear susceptibility x(3) ~ 10-11-10-10 esu.
PUBLISHED
Keywords: nitrogen laser; nitrogen laser